The Relationship Between Business Strategy Formulation and Financial Rasios in Assessing the Performance of PT Vale Indonesia Tbk - Borahima, Bahrun; Haritsar, Yosar; Saifuddin, Saifuddin; Hario, Raden (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
In order to evaluate PT Vale Indonesia Tbk's performance as a major player in the mining industry, this study attempts to unearth new data and explore significant aspects of the relationship between financial ratios and business strategy development. This study uses a quantitative descriptive methodology to conduct a case study on PT Vale Indonesia Tbk. Describe and assess the financial reports for 2020–2023 that are accessible on the Indonesian Stock Exchange. A company's success is largely determined by how well its financial implementation discipline and strategic planning work. These initiatives have a positive impact on key financial ratios through enhanced operational efficiency, increased liquidity, and increased profitability. The company's low debt-to-equity ratio is increasingly indicative of its excellent financial management and resilience. Additionally, PT Vale Indonesia Tbk has made governance, society, and the environment its top strategic priorities. This study is unique in that it examines the creation of sustainable business plans and the performance of PT Vale Indonesia Tbk during the national nickel downstream initiative using financial ratios. PT Vale ensures regulatory compliance while fostering innovation in ethical mining. Additionally, the strategic focus of PT Vale Indonesia Tbk is on ESG (Environmental, Social, and Governance)-based plans for the mining industry.